Oil Palm Pressed Fiber Valorization: Improving Fiber Processing in Composting with Azotobacter for Use in Potting Media of Brassica rapa - Sylvia Madusari; Zakat Firmanto; Rufinusta Sinuraya (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2020)
Fiber (mesocarp fiber) is a solid waste generated in the oil palm factory which potentially used as fertilizer through composting. Addition of Azotobacter sp. in composting can increase nitrogen content, which improve the quality of compost. The purpose of this research was to determine the effect of the enrichment of Azotobacter sp. in composting of oil palm pressed fiber and analyzing the nutrient content and its potential as a planting medium of pakcoy (Brassica rapa). Descriptive method was used in the process of composting by assessing the physical and chemical properties of the compost produced. Fiber compost testing as a planting medium was carried out using a nonfactorial Randomized Complete Block Design in 3 variations of 30%, 50% and 70% treatment, and each mixed with subsoil. The results of compost physical parameters analysis showed the dark brown color, and the texture showed more crumb in the compost enriched with Azotobacter sp. The best pH was found in the compost treated with the addition of Azotobacter sp., which was 8.36. Analysis of compost application on pakcoy growth showed that the highest leaf area (69.73 cm2) and number of stomata (36.4 mm2)-1) were found in the F2P2 treatment (Azotobacter Fiber Compost 50% + Subsoil 50%); The highest root length (28.38 cm), shoot dry weight (2.58 g), and root dry weight (2.26 g) were found in the F2P3 treatment (Azotobaacter Fiber Compost. 70% + Subsoil 30%). From the results of these experiments, the compost enriched with azotobacter has beneficial effects on crop growth could be attributed to soil amendments.